Studi Pemanfaatan Campuran Serbuk Tempurung Kelapa dan Serat Bambu untuk Material Alternatif Kampas Rem Sepeda Motor - Muhammad Cahya Wicaksana; Xander Salahudin; Fuad Hilmy (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The manufacturing industry in Indonesia has experienced significant growth. This increase has also impacted the demand for motorcycle spare parts. Currently, brake pads are composed of asbestos, which makes them prone to overheating and failure when reaching high friction temperatures. Therefore, an alternative brake pad material is an organic material mixed with coconut shell powder and bamboo fiber. This study aims to analyze the wear and hardness levels of motorcycle brake pads made from coconut shell powder and bamboo fiber. The study used varying ratios of coconut shell powder, bamboo fiber, and epoxy resin: 40:30:30, 35:35:30, and 30:40:30. Eighteen specimens were tested. Wear testing was performed using an Ogoshi Wear Tester, while hardness testing was performed using a Brinell hardness tester. The test results showed that the smallest wear rate on brake pads with variations of 40% coconut shell powder, 30% bamboo fiber and 30% epoxy resin was 0.001107984 mm3/kg.m. The highest hardness level was also in the variation of 40% coconut shell powder, 30% bamboo fiber and 30% epoxy resin at 63,0024 kg/. So it can be concluded that the greater the percentage of coconut shell powder and the smaller the percentage of bamboo fiber, the lower the wear rate. If the greater the percentage of coconut shell powder and the smaller the percentage of bamboo fiber, the higher the hardness level. So it can be concluded that a good brake pad variation is a variation of 40% coconut shell powder, 30% bamboo fiber and 30% epoxy resin.